Developing Addie Model: Speaking for Informal Interaction Based on OBE Curriculum - Ni Wayan Krismayani; Dewa Ayu Ari Wiryadi Joni; I Komang Budiarta (Universitas Hamzanwadi, 2023)
Coursebook plays an essential role in English language teaching. It is a guide to the prescribed curriculum and syllabus. However, the coursebook does not always match the needs of students and lecturers. This study aims to develop a speaking coursebook using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model based on OBE Curriculum. Researchers used Research and Development (R&D) in which the data were collected through questionnaire and interview. There were 26 students and two lecturers in the English Language Education Study Program. From the finding, the design and development of the coursebook are highly influenced by the result of the needs analysis. From the impact of the need analysis, the researchers developed the coursebook for Speaking for Informal Interaction that provides achievable teaching ideas for lecturers, including speaking activities, vocabulary, grammar, dialogue examples, exercise (individual, pair, or group work), and lesson learned related to the topics discussed. The result of validation from experts (design, content, and language), students, and lecturers agreed that the coursebook had met the criteria of a good coursebook. The results of this study can later be effectively used to support the achievement of student communicative competence, especially in the Speaking for Informal Interaction course.